Delivery of Fluorescent Probes Using Streptolysin O for Fluorescence Microscopy of Living Cells. (30th July 2018) - Teng, Kai Wen; Ren, Pin; Selvin, Paul R.
Abstract: Methods to efficiently deliver fluorophores across the cell membrane are crucial for imaging the dynamics of intracellular proteins using fluorescence. Here we describe a simple protocol for permeabilizing living cells using streptolysin O, a bacterial toxin, which allows transient uptake of fluorescent probes for labeling specific intracellular proteins. The technique is applicable for delivering different classes of fluorescent probes with a molecular weight of <150 kDa, and it is also applicable to a variety of different cell lines. The technique enables the utilization of a broad range of fluorophores for live cell imaging of intracellular proteins. Extended observation of intracellular fluorescence bound to specific proteins is now possible through super‐resolution microscopy by using fluorophores that are photostable in "cell‐friendly" deoxygenating and reducing conditions. © 2018 by John Wiley & Sons, Inc.